'United Britons & Irishmen': Cato Street, Proclamations, and the Insurrectionary Tradition, 1798–1820. (11th October 2021) - McElligott, Jason
Abstract: This article describes attempts in 1820 by a group of London‐based conspirators to assassinate the British cabinet and print two proclamations declaring the establishment of a provisional government. One proclamation was addressed to the civilian population and the other to the rank and file of the military. It describes links between these conspirators, who were arrested in Cato Street on 23 February 1820, and a number of Irish radicals living in the metropolis who claimed to have been involved in the rebellions of 1798 and 1803. It suggests that the Cato Street proclamations were strongly influenced by John Sheares's proclamation of 1798, which had been intended to announce the success of the Irish rebellion.